The structural deficit: methodological problems and political implications - Heimberger, Philipp (Momentum Quarterly, 2014)
The structural budget balance is a main control indicator of the EU’s fiscal regulation framework. Fiscal policy restrictions which are based on the budget balance corrected for cyclical and one-off effects give special importance to forecast deviations and ex-post corrections of the structural budget balance. This paper examines revisions during the years of economic crisis with regard to the underlying methodical problems and discusses the political implications. Estimating output potential is the main methodical problem. Over the last couple of years, the European Commission has underestimated the size of negative output gaps, which leads to overestimations of structural deficits. Because of the high revision sensitivity of structural deficit estimations, restrictive structural deficit limits which are legally binding remain questionable.
Keywords: Structural deficit; Fiscal regulation framework in the EU; Fiscal policy